2015
DOI: 10.1039/c5cc03944d
|View full text |Cite
|
Sign up to set email alerts
|

Bi- and trimetallic rare-earth–palladium complexes ligated by phosphinoamides

Abstract: The synthesis of the heterometallic early-late 4d/4f bi- and trinuclear phosphinoamido Ln-Pd(0) complexes [(Ph2PNHPh)Pd{μ-(Ph2PNPh)}3Ln(μ-Cl)Li(THF)3] (Ln = Y, Lu) and [Li(THF)4][{(Ph2PNHPh)Pd}2{μ-(Ph2PNPh)}4Ln] (Ln = Y, Lu) is described. The latter compounds are the first early-late trimetallic phosphinoamido complexes. Although the metal atoms are forced into close proximity by the phosphinoamido ligands, quantum chemical calculations show only weak metal-to-metal interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 33 publications
2
45
0
Order By: Relevance
“…At large distances, the model complex dissociates into the expected units composing of highly ionic Cp 2 ZrF 2 and two [(PMe 3 )AuCl] molecules (the potential energy curve is given in Figure S1 of the Supporting Information). Comparable to the Lu/Pd system reported before, the long‐range interaction shows R −2 behaviour, which is typical for a charge–dipole interaction. Due to our understanding of the Lu/Pd system, we interpret the bonding between Zr and Au in 6 to be comparably weak…”
Section: Resultssupporting
confidence: 45%
See 2 more Smart Citations
“…At large distances, the model complex dissociates into the expected units composing of highly ionic Cp 2 ZrF 2 and two [(PMe 3 )AuCl] molecules (the potential energy curve is given in Figure S1 of the Supporting Information). Comparable to the Lu/Pd system reported before, the long‐range interaction shows R −2 behaviour, which is typical for a charge–dipole interaction. Due to our understanding of the Lu/Pd system, we interpret the bonding between Zr and Au in 6 to be comparably weak…”
Section: Resultssupporting
confidence: 45%
“…The synthesis of heterometallic ELHBs usually requires ligand systems which take the different affinities of the metals for certain donor atoms into account. Typically, soft donor centres (phosphines, NHCs or thiolates) are combined with hard donor centres (alkoxides, amidinates) on a common backbone . Another possibility is the synthesis of a mono‐ or polynuclear complex which can function as a metalloligand for the coordination of other metals .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterobimetallic Pd−Ln complexes have recently been reported for yttrium and lutetium, but the scandium congener has hitherto been unknown. The reported Pd−Y and Pd−Lu distances were 2.98–3.18 Å and 2.97 Å, respectively, longer than that in 2 if the different ionic radii of Sc 3+ (0.745 Å), Y 3+ (0.900 Å), and Lu 3+ (0.861 Å) are considered . The short Pd−Sc distance in 2 can be attributed to the very low coordination number at the Lewis acidic Sc 3+ , withdrawing electron density from the Lewis basic Pd 0 center for stability.…”
Section: Resultsmentioning
confidence: 95%
“…Recent studies have shown that phosphinoamido and phosphine‐functionalized amido ligands can support LM−Ln bonding interactions. Although only weak interactions are involved in the case of the complex shown in Figure d, stronger Ni→Lu interactions have been shown to influence catalytic activity by varying the coordination sphere of the Lu 3+ center (Figure e) …”
Section: Introductionmentioning
confidence: 99%